The fae princes eaudiobook - St. Crowe, Nikki (Vicious Lost Boys, 2023)
I thought Peter Pan was a myth and Neverland a fairytale. A story spun by my mother who had lost her mind a long time ago. But there was no denying the overwhelming shadow cast by Peter Pan when he was standing in my house. Pan took me captive to Neverland and I somehow found my place among him and the Lost Boys. I've never looked back. Now I'm entangled right alongside him in a war we can't seem to escape. We thought we had defeated our enemies. We thought we could finally have our happily ever after. But there was one enemy we never saw coming. A fairy who has nothing to lose and everything to gain. The fairy with golden wings and a dark, twisted heart. She wants Neverland and she'll stop at nothing to have it. Including destroying anyone who stands in her way, even her own flesh and blood. NOTE: The Fae Princes is a reimagining of Peter and Wendy. Characters have been aged up for this darker, grittier version. If you like your enemies to lovers romance with hot, ruthless, morally gray love interests, you'll enjoy this series. You can expect hate kissing, fighting, bickering, and 'touch her and I'll unalive you' vibes. The Fae Princes is the final book in the main storyline for the Vicious Lost Boys Series. Please check the author's website for CWs.